2014
DOI: 10.2478/rjdnmd-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins: Good Markers for Cardiovacular Risk in Patients with Chronic Kidney Disease and Dyslipidemia

Abstract: Background and aims. Dyslipidemia (DLP) is a common complication of chronic kidney disease (CKD) and may accelerate its progression. Circulating lipoproteins and their constituent proteins, apolipoproteins, are risk factors for CKD and cardiovascular diseases (CVD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…5 Severe lipid metabolism disorders arise in patients with kidney failure and the lipid metabolism disorder peculiar to this patient group is known as uraemic dyslipidaemia, 5 which may accelerate its progression. 6 Abnormal lipid profile in CKD includes hypertriglyceridaemia, increase in triglyceride remnant Lp (a), increase in VLDL, decrease in HDL, total cholesterol and LDL usually within normal limits except in nephrotic syndrome patients. 7 The association between lipid profile and severity of CKD has rarely been studied in a general population, especially in our part of the country and may have a future prognostic and management implication in patients with CKD.…”
mentioning
confidence: 99%
“…5 Severe lipid metabolism disorders arise in patients with kidney failure and the lipid metabolism disorder peculiar to this patient group is known as uraemic dyslipidaemia, 5 which may accelerate its progression. 6 Abnormal lipid profile in CKD includes hypertriglyceridaemia, increase in triglyceride remnant Lp (a), increase in VLDL, decrease in HDL, total cholesterol and LDL usually within normal limits except in nephrotic syndrome patients. 7 The association between lipid profile and severity of CKD has rarely been studied in a general population, especially in our part of the country and may have a future prognostic and management implication in patients with CKD.…”
mentioning
confidence: 99%
“…In the general population, several clinical studies (e.g., AMORIS (Apolipoprotein-related MOrtality RISk) [38] or INTERHEART [39]) have shown that the ApoB/ApoA-I ratio is strongly correlated with cardiovascular events such as myocardial infarction and stroke [40].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…Disturbances in lipoprotein metabolism are evident even in the early stages of CKD and usually follow a downhill course that parallels the deterioration in renal function [11]. Severe lipid metabolism disorders arise in patients with kidney failure and the lipid metabolism disorder peculiar to this patient group is known as uremic dyslipidemia [11], which may accelerate its progression [12]. Abnormal lipid profile in CKD includes hypertriglyceridemia, increase in triglyceride remnant Lp (a), increase in very-low-density lipoprotein (VLDL), decrease in high density lipoprotein (HDL), total cholesterol (TC) and low-density lipoprotein (LDL) usually within normal limits except in nephrotic syndrome patients [13].…”
Section: Introductionmentioning
confidence: 99%